PERILAKU KOROSI PANAS BAJA AISI 4130 PADA TEMPERATUR 750 O C DALAM LINGKUNGAN ATMOSFER YANG MENGANDUNG KLOR DAN SULFUR - Yusuf, Muhammad Ihsan (Jurnal Ilmiah Teknik Mesin FEMA, 2014)
Steel is the main material of an industry. In a world of steel metallurgy has a character different from the microstructure to mechanical properties. It is therefore very important to know well the character of a steel that can be used as needed. If it is not appropriate in selecting a material, there will be a failure. In this study the oxidation testing AISI 4130 steel at a temperature of 750 C in NaCl/Na2SO4 environment. Tests performed to see the length of time gain against corrosion, and oxidation product analyzes performed by the method of X-RD, SEM/EDS and OM. These results indicate that the oxide formed shows : Fe2O3, Fe3O4, FeO, and Cr2O , the steel surface is almost the same for all the specimens were oxidized in a different environment. The existence of deposits of NaCl and Na2SO4 deposits on the surface of AISI 4130 steel can accelerate the oxidation process at high temperature. The existence of chlorine gas and sulfur gas in the atmosphere causing the surface layers of AISI 4130 steel is oxidized more rapidly than those occurring in ordinary air environment. Damage to the surface layer of AISI 4130 steel is exacerbated by the growth of iron rich oxide (Fe2O3) on the protective layer. Formation is accelerated by reaction Fe and FeOCr2O3 formation on AISI 4130 steel with a deposit of NaCl and Na2SO4 deposits. Keywords: Steel AISI 4130, NaCl deposit, Na2SO4, deposits, Fe2O3